Im Dialog: Theologische Grundlagen und religionsdidaktische Impulse für die Praxis des kokoRUs. Rezension zu Bernd Schröder/Jan Woppowa (Hg.): Theologie für den konfessionell-kooperativen Religionsunterricht. Ein Handbuch, Tübingen 2021 - Neumann, Anna (Praktische Theologie. Zeitschrift für Praxis in Kirche, Gesellschaft und Kultur)

All optical operation of a superconducting photonic interface - Thiele, Frederik; Hummel, Thomas; McCaughan, Adam N.; Brockmeier, Julian; Protte, Maximilian; Quiring, Victor; Lengeling, Sebastian; Eigner, Christof; Silberhorn, Christine; Bartley, Tim (Optics Express)
Quantum photonic processing via electro-optic components typically requires electronic links across different operation environments, especially when interfacing cryogenic components such as superconducting single photon detectors with room-temperature control and readout electronics. However, readout and driving electronics can introduce detrimental parasitic effects. Here we show an all-optical control and readout of a superconducting nanowire single photon detector (SNSPD), completely electrically decoupled from room temperature electronics. We provide the operation power for the superconducting detector via a cryogenic photodiode, and readout single photon detection signals via a cryogenic electro-optic modulator in the same cryostat. This method opens the possibility for control and readout of superconducting circuits, and feedforward for photonic quantum computing.
Keywords: Atomic and Molecular Physics; and Optics

Kompromisse vor dem Kompromiss: Friedensstiftung im hohen Mittelalter - Kamp, Hermann (Kompromissfindung in der Literatur und Kultur des Mittelalters: Strategien und Narrative zwischen Zweifel, Dissens und Aporie)

Investigation regarding the correlation of the relative influences during the extrusion process of cast films on the residual melt quality - Schöppner, Volker; Trienens, Dorte

Psychologie - Gretz, Daniela (Theodor-Fontane- Handbuch)

Rezeption zu Lebzeiten - Gretz, Daniela (Theodor- Fontane-Handbuch)

Beteiligung im Onlineunterricht in der Berufsfachschule. - Sommer, Sabrina; Förster, Anika (Therapie Lernen)

Schulkulturbezogene Schultypen im Zeitalter der digitalen Transformation. Eine Typologie unter Berücksichtigung von Hintergrundmerkmalen der zur Schulkultur befragten Lehrkräfte - Caruso, Carina; Drossel, Kerstin; Heldt, Melanie (MedienPädagogik)
In view of technological progress, a digitalisation deficit in German schools as well as the experiences in schools as a result of the Corona pandemic, it becomes apparent that the question of a school culture conducive to learning retains its relevance in the age of digital transformation: On the one hand, it is evident that school culture changes in view of the digital transformation. On the other hand, it contributes to the successful implementation of digital media. Previous research findings in connection with the digital transformation focus on particular competencies of teachers (Meyer, Becker, and Bock 2023; Caruso, Heldt, and Drossel 2022; Vogelsang et al. 2023) and their cooperative behaviour (Drossel and Heldt 2022; Schulze, Drossel, and Eickelmann 2022). These questions whether school culture-related school types can be identified or not and how teachers perceive the school culture have been less considered so far. This article is dedicated to this question and explores if the school culture-related school types differ in terms of the background characteristics of the teachers. Based on a Latent Class Analysis, three school culture-related school types become apparent: strong in innovation and cooperation (Type I: 45.74 %), highly innovative and inhibited cooperation (Type II: 17.95 %), inhibited in terms of innovation and cooperation (Type III: 36.31 %). The types do not differ from each other regarding the background characteristics.

Gemeindereferent_innen als Katalysator einer Transformation von Kirche? Professionsbezogene Perspektiven - Caruso, Carina; Hobelsberger, Hans (Gemeindereferent:in. Kompetenzen und Potenziale eines unterschäzten Berufs. Eine Studie zu Berufsbild und kirchlich-pastoraler Transformation)

Design und Ergebnisse des qualitativen Studienteils - Jung , Jennifer; Caruso, Carina (Gemeindereferent:in. Kompetenzen und Potenziale eines unterschätzten Berufs. Eine Studie zu Berufsbild und kirchlich-pastoraler Transformation)

Elisabetta Lupi, Jonathan Voges (Eds.), Luxus. Perspektiven von der Antike bis zur Neuzeit - Harnack, Maria

Forderer, Tanja, Was Gott zusammengefügt hat...? Eine argumentationsanalytische Untersuchung von Ehe-Scheidung im Neuen Testament am Beispiel von Mk 10,1–12 und 1Kor 7,10–16 - Breuer, Saskia Rebecca (Theologische Revue)

Einführung - Breuer, Saskia Rebecca; Paul, Clarissa; Schmidt, Eckart (Konflikte und Krisen im Neuen Testament und ihre Bewältigungsstrategien)

Leitlinien für einen armuts- und gendersensiblen Religionsunterricht. Reflexionshilfen zur Praxis inklusiver religiöser Bildung - Uppenkamp, Vera; Knauth, Thorsten (Religiöse Bildung an den Rändern der Vielfalt. Soziale Benachteiligung, Religion, Geschlecht)

Zwischen Inklusion und Distinktion. Armutssensibler Religionsunterricht unter Berücksichtigung genderbezogener Aspekte - Uppenkamp, Vera (Religiöse Bildung an den Rändern der Vielfalt. Soziale Benachteiligung, Religion, Geschlecht)

Frühe Versuche zur Etablierung des Hochschulstandorts Paderborn (1945-1970) - Grüttner, Niclas Christian (50 Jahre Universität Paderborn. Studentische Forschungsprojekte zur Gründungsgeschichte. Ein Rückblick)

Heterogeneous Structural Evolution of In–Zn–O Thin Films during Annealing - Moffitt, Stephanie L.; Cao, Chuntian; Van Hest, Maikel F. A. M.; Schelhas, Laura T.; Steinrück, Hans-Georg; Toney, Michael F. (The Journal of Physical Chemistry C)
Keywords: Surfaces; Coatings and Films; Physical and Theoretical Chemistry; General Energy; Electronic; Optical and Magnetic Materials

An eigenen Fällen lernen. Überlegungen zur lern- und entwicklungsorientierten Fallarbeit in der Religionslehrer:innenbildung - Caruso, Carina; Woppowa , Jan (Religionslehrer:in im 21. Jahrhundert. Transformationsprozesse im Beruf und theologisch-religionspädagogischer Bildung in Studium, Referendariat und Fortbildung)

Integrative conceptualization of products and business models for the circular economy: A systematic literature review - Scholtysik, Michel; Koldewey, Christian; Rohde, Malte; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

Die Transformation zum Smart Service-Anbieter - Scholtysik, Michel; Koldewey, Christian; Dumitrescu, Roman; Rasor, Anja; Ködding, Patrick; Wegel, Arthur; Fischer, Lena